Determination of Inhibitory Effects of Allium sativum Extract on Biofilm Production by Clinical Staphylococcus aureus Isolates (Tribhuvan University Journal of Microbiology, 2021)
Objectives: To determine anti-biofilm effect of fresh garlic extract (FGE) on Staphylococcus aureus biofilm production and the relationship between methicillin resistance and biofilm production intensity.Methods: Clinical S. aureus isolates were identified methicillin resistant S. aureus (MRSA) by cefoxitin disc diffusion method. The anti-biofilm effects of FGE on S. aureus biofilm biomass determination was done using crystal violet assay.Results: Among 71 S. aureus isolates, MRSA were 37 (52.1%). Among biofilm producers, comparison of biofilm biomass (absorbance at 492 nm) showed no significant differences in biofilm formation ability between MRSA and MSSA (p=0.325). Use of 10% FGE decreased biofilm production in MRSA and MSSA by 40.4% (p